Determination of Conventional Transportation for ADL Pathway in Malang City - Suta Dwi Atmawiyanur; Nelly Budiharti; Emmalia Adriantantri (Institut Teknologi Sepuluh Nopember, 2020)
The number of conventional microbus transports with passengers can be seen from the comparison between capacity in a trip t.hat is far from the capacity standard. This study uses the Work Sampling and Work Load Analysis theory to determine the optimal needs of the microbus ADL (Arjosari - Dinoyo - Landungsari) route. The study was conducted by observation and interview. The study was conducted by taking samples of microbus and microbus drivers as many as 38 unit of the total number of drivers and minibus available is 42 unit. Data collection by following the driver's activities for 5 days commuting. Record the number of passengers and the productive and non-productive time of the driver by taking into account the Performance Rating and Allowance factors and calculating the driver's workload. The results showed an average driver workload only 49 % with the current active microbus condition with total of 42 units. The researcher recommends that each minibus driver has an ideal workload of 90%, so the need for ADL line microbuses is 23 units in the hope that the number of passengers will increase.